2006
DOI: 10.1038/ncb1446
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin relaxation in response to DNA double-strand breaks is modulated by a novel ATM- and KAP-1 dependent pathway

Abstract: The cellular DNA-damage response is a signaling network that is vigorously activated by cytotoxic DNA lesions, such as double-strand breaks (DSBs). The DSB response is mobilized by the nuclear protein kinase ATM, which modulates this process by phosphorylating key players in these pathways. A long-standing question in this field is whether DSB formation affects chromatin condensation. Here, we show that DSB formation is followed by ATM-dependent chromatin relaxation. ATM's effector in this pathway is the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
703
5
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 655 publications
(747 citation statements)
references
References 35 publications
38
703
5
1
Order By: Relevance
“…It is becoming evident that while the cellular response to DNA damage relies on a core of DDR-dedicated proteins, many of its arms are based on temporary recruitment of proteins or functional modules that normally operate in other processes. Indeed, it has been shown that the DDR temporarily calls into action proteins that normally act in other contexts, such as gene expression [29][30][31][32][33][34][35] or RNA metabolism [36]. This means that the DDR pulls players from various cellular processes out of their regular context and assigns them temporary tasks under its command.…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming evident that while the cellular response to DNA damage relies on a core of DDR-dedicated proteins, many of its arms are based on temporary recruitment of proteins or functional modules that normally operate in other processes. Indeed, it has been shown that the DDR temporarily calls into action proteins that normally act in other contexts, such as gene expression [29][30][31][32][33][34][35] or RNA metabolism [36]. This means that the DDR pulls players from various cellular processes out of their regular context and assigns them temporary tasks under its command.…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
“…DNA repair is no exception, and dynamic changes in chromatin condensation and accompanying histone marks have been recognized as inevitable DDR pathways [15,[75][76][77][78][79][80]. Here, too, the DDR relies on recruitment of existing players in the chromatin organization arena [32][33][34][75][76][77][78][79][81][82][83][84][85]. H2B monoubiquitylation was previously implicated in the DDR in the budding yeast [86][87][88].…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
“…Identification of ATM-dependent chromatin relaxation via KAP-1 activity following DNA damage has further demonstrated the dependence of DNA repair on alteration of chromatin structure. ATM phosphorylates KAP-1 on Ser 824, and ablation of this site was demonstrated to abolish DSB-induced chromatin relaxation and resulted in cellular hypersensitivity to DSB-inducing agents (Ziv et al, 2006). Moreover, ATM has also been implicated in regulating ordered chromatin changes after DNA breaks to facilitate DNA repair (Berkovich et al, 2007).…”
Section: Defective Dna Dsb Responses and A-t-related Syndromesmentioning
confidence: 99%
“…Such pleiotropic effects of ATM are attributable to a wide range of its substrates including Chk2, p53, mdm2, NBS1, SMC1, FANCD2, Kap1, BRCA1 and others, all components of DNA damage signalling, repair, chromatin remodelling, transcriptional regulation, apoptosis and other mechanisms that together constitute the multifaceted cellular response to DNA damage (Shiloh, 2003;Ziv et al, 2006;Matsuoka et al, 2007). Consistent with its role in genome stability maintenance, ATM is also an established tumour suppressor whose mutations or epigenetic silencing contributes to pathogenesis of a range of malignancies (Shiloh, 2003;Kastan and Bartek, 2004).…”
Section: Introductionmentioning
confidence: 99%